Analysis of human information acquisition behavior for natural gaze-based wheelchair control - Jipp, Meike; Bartolein, Christian; Badreddin, Essameddin (Proceedings of the Human Factors and Ergonomics Society 52nd annual meeting, 2008)
Especially for severely disabled people, a powered wheelchair is an important means to participate in societal life and live as far as possible independently. To achieve this goal for users, who cannot operate their wheelchair with the traditional joystick or specialty controls, methods have been developed to enablesteering the wheelchair on the basis of the user’s gaze behavior. While existing approaches require the user to adapt his/her gaze behavior to match the characteristics of the human-technology interaction and/or only provide reasoning about the desired motion direction of the user, the conducted study gives crucial input about the relationship between the gaze behavior of wheelchair users and the - from the user - desired goal position as well as his/her anticipated mission. Implications for a natural gaze-based assistance system for electrically powered wheelchairs are drawn, which allows reasoning on the user’s behavioral goal position and his/her current mission.